The effects of twisted strips with different length on heat transfer and pressure drop in concentric heat exchanger - Argunhan, Zeki; Yıldız, Cengiz; El, Emin (Bitlis Eren University, 2025)
This study investigated the use of twisted strips as passive turbulators to improve heat transfer efficiency in concentric heat exchangers. In the experiments, four different lengths of twisted strips were designed (l = 0.25 m, 0.5 m, 0.75 m, and 1 m) and their performance was evaluated in a system with air and water fluids. The effects of twisted strips on heat transfer and pressure drops are investigated in both parallel and countercurrent flow patterns, and the results are analyzed in terms of Nusselt and Reynolds numbers. The results indicated that tubes using twisted strips achieved significant increases in the heat transfer coefficient compared to straight tubes. The highest increase in heat transfer performance reached 78% when the length of the twisted strip was l/L=1. The Nusselt number increased by a factor of 1.2 to 1.8, depending on the length of the twisted strips. The shortest strip length (l/L=0.25) resulted in the lowest heat transfer performance. However, these improvements were accompanied by significant increases in pressure drop; for full-length strips, the pressure drop increased by nearly 100%. The pressure drop increased slightly as the Reynolds number increased. The swirling flow generated by the twisted ribbons plays an important role in increasing the heat transfer. Despite the increases in pressure drops, the energy loss is negligible compared to the heat transfer gain achieved. In conclusion, the length ratio of the twisted strips significantly affects the thermal performance of the heat exchanger while increasing the pressure losses. These findings demonstrate the effectiveness of twisted strips as passive turbulators.
Keywords: Energy Generation; Conversion and Storage (Excl. Chemical and Electrical); Enerji Üretimi; Dönüşüm ve Depolama (Kimyasal ve Elektiksel hariç)